Strategi Marketing Public Relations dalam Aktivitas Branding Super Air Jet Indonesia - Siregar, Repli; Erwina, Wina; Setianti, Yanti (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
Super Air Jet Indonesia is a commercial airline that was officially established in 2021. As a new company it is very important to build and introduce its brand to the public in order to create a positive image to strengthen the Super Air Jet brand. Brand building activities are one of the important roles of marketing public relations where the focus is not on sales activities but rather on the function of marketing synergy. So this research focuses and aims to see how Super Air Jet implements marketing public relations strategies in its branding activities. In this research, researchers conducted in-depth interviews and carried out non-participatory observations supported by several secondary data in the form of documentation. The results of this research highlight the branding activities carried out by Super Air Jet from the marketing public relations strategy. The push strategy carried out by Super Air Jet is through collaboration with other companies, one of which is the travel agent company. Super Air Jet Indonesia also establishes relationships with the media as a form of its push marketing public relations strategy. Super Air Jet's pull marketing public relations strategy is in the form of give away to its followers on Instagram. The pass strategy, Super Air Jet actively organizes marketing events such as birthday celebrations which include fashion shows for Super Air Jet flight attendants. Super Air also participated in the Run Hub event by becoming a sponsor partner with other Lion Group subsidiaries. And finally, Super Air Jet also collaborates with content creators to create content related to Super Air Jet so that coverage of Super Air Jet continues to expand on social media.